0946 Parent-Perceived Sleep Problems Associated with Common Medical Issues During Infancy. (27th May 2020) - Mindell, J A; Leichman, E S; Williamson, A A; Gould, R A; Hiscock, H; Quach, J
Abstract: Introduction: Sleep problems are highly prevalent during infancy. However, little research has been conducted on associations between these sleep issues and common medical concerns in early development. Thus, the purpose of this study was to assess the prevalence of parent-perceived sleep problems in infants with common medical problems. Methods: Participants were 5, 097 children from the Longitudinal Study of Australian Children—Birth Cohort. Caregiver-reported child sleep problems and medical concerns were assessed at ages 0-1 year. Chi-square analyses were used to examine associations between the presence of a parent-perceived sleep problem and medical concerns. Results: Wheezing (29.6%), eczema (14.9%), and food/digestive allergies (5.0%) were the most commonly identified medical concerns. In addition, 17.1% of caregivers reported a moderate/severe child sleep problem. Infants who had a moderate to severe parent-identified sleep problem experienced higher rates of overall medical care/needs, wheezing, eczema, food/digestive allergies ( p <.001), ear infections ( p <.05), and other illnesses ( p <.01) than those infants without a sleep problem. No differences were observed with regard to hearing problems, vision problems, developmental delay, diarrhea/colitis, anemia, or other (non-ear) infections. Furthermore, parents reported higher rates of sleep problems for infants with medical problems (20.0-37.5%) than for infants without medical problems (16-17%), especially related to needing medical care (sleep problems = 27%), food/digestive allergies (27%), eczema (23%), and wheezing (20%), p =.001. Conclusion: Overall, common medical issues during infancy, including food/digestive allergies, eczema, and wheezing, are associated with greater parent-endorsed child sleep problems. Primary care providers should assess for and address sleep problems when treating common medical concerns during infancy. Support: This project was partially supported by Johnson and Johnson Consumer Health (JAM, ESL, and RAG) and NIH K23HD094905 (AAW).